Characterization of Polyhydroxyalkanoates Produced at Pilot Scale From Different Organic Wastes - Lorini, Laura; Martinelli, Andrea; Capuani, Giorgio; Frison, Nicola; Reis, Maria; Sommer Ferreira, Bruno; Villano, Marianna; Majone, Mauro; Valentino, Francesco (Frontiers in Bioengineering and Biotechnology, 2021)
Polyhydroxyalkanoates (PHAs) production at pilot scale has been recently investigated and carried out exploiting different process configurations and organic wastes. More in detail, three pilot platforms, in Treviso (North-East of Italy), Carbonera (North-East of Italy) and Lisbon, produced PHAs by open mixed microbial cultures (MMC) and different organic waste streams: organic fraction of municipal solid waste and sewage sludge (OFMSW-WAS), sewage sludge (SS) and fruit waste (FW), respectively. In this context, two stabilization methods have been applied, and compared, for preserving the amount of PHA inside the cells: thermal drying and wet acidification of the biomass at the end of PHA accumulation process. Afterwards, polymer has been extracted following an optimized method based on aqueous-phase inorganic reagents. Several PHA samples were then characterized to determine PHA purity, chemical composition, molecular weight, and thermal properties. The polymer contained two types of monomers, namely 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV) at a relative percentage of 92.6–79.8 and 7.4–20.2 w/w, respectively, for Treviso and Lisbon plants. On the other hand, an opposite range was found for 3HB and 3HV monomers of PHA from Carbonera, that is 44.0-13.0 and 56.0-87.0 w/w, respectively. PHA extracted from wet-acidified biomass had generally higher viscosity average molecular weights (Mv) (on average 424.8  20.6 and 224.9  21.9 KDa, respectively for Treviso and Lisbon) while PHA recovered from thermally stabilized dried biomass had a 3-fold lower Mv.